Anti-inflammatory properties of Amomum maximum Roxb and Amomum muricarpum Elmer in the North of Vietnam - Thu, Pham Anh; Son, Nguyen Hoang; Huong, Le Thanh; Dang, Nguyen Hai (Vietnam Journal of Biotechnology, 2021)
Inflammation is the body's homeostatic defense mechanism in which the immune system reacts to remove foreign bodies. Chronic inflammation can increase the risk for additional damage like autoimmune diseases, arthritis, diabetes and can result in death. Amomum maximum Roxb and Amomum muricarpum Elmer distributed widely in Vietnam have been used in traditional medicine for treatment of some gastrointestinal diseases. This study aimed to investigate the anti-inflammatory effects of the methanol extracts of A. maximum (AMM) and A. muricarpum Elmer (AMC) in murine macrophage RAW 264.7 cell line. The total extracts showed that the extracts exhibited low cytotoxicity and potent anti-inflammatory activities by suppressing excessive nitric oxide (NO). The IC50 values of AMC and AMM were found to be 12.67 ± 1.7 µg/mL and 42.7 ± 2.5 µg/mL, respectively. To elucidate the underlying mechanism, the expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were evaluated using Western blot analysis. Our data demonstrated that AMC reduced the inflammatory response in a lipopolysaccharide (LPS)-induced RAW264.7 cell model via inhibition of iNOS and COX-2 while AMM seemed to modulate the inflammatory effect through the iNOS pathway only. In conclusion, AMM and AMC root extracts might be potential candidates for a study of naturally alternative anti-inflammatory drugs.